The efficacy of natalizumab in patients with multiple sclerosis according to level of disability: results of an observational study. - Fernández Fernández, Óscar; Papais Alvarenga, Marcos; Guerrero, Miguel; León, Antonio; Alonso, Ana; López-Madrona, Jose Carlos; Leyva-Fernández, Laura; Oliver-Martos, Begoña; De Ramón, Enrique; Luque, Gloria; Fernández, Victoria (Sage Publications, 2010)
Background: Little is known about how the level of disability at the start of treatment with natalizumab affects its efficacy. Objectives: The aim of this study was to investigate the effect of natalizumab on relapses in patients with different levels of baseline disability associated with MS. Methods: This single-centre observational study collected demographic data for patients followed prospectively and who were scheduled to start natalizumab therapy due to the presence of disease activity. The annualized relapse rate (ARR) and Kurtzke Expanded Disability Status Scale scores were analysed for the previous year, on starting treatment (baseline) and 1 year after starting therapy. Results: Seventy-seven patients (mean age: 39.0 years, mean disease duration: 12.4 years) were included. The difference between ARR before and after starting treatment was 0.92 for baseline Expanded Disability Status Scale ≤3.5 (p < 0.0005), 0.70 for Expanded Disability Status Scale 4.0–6.0 (p < 0.007) and 0.57 for Expanded Disability Status Scale ≥6 (p = 0.386). Expanded Disability Status Scale did not vary during the study. One patient discontinued treatment due to an adverse event and nine patients discontinued due to positive anti-natalizumab antibodies. Conclusions: The findings support the efficacy of natalizumab in reducing ARR in the year after starting treatment in patients with baseline Expanded Disability Status Scale ≤6.
Keywords: Esclerosis múltiple - Tratamiento; Natalizumab; Relapsing–remitting multiple sclerosis; Secondary–progressive multiple sclerosis